The Correlation Between Construction Management Efficacy and Hydraulic Design Compliance with Cost Overruns in Public-Private Partnership (PPP) Water Supply Projects - Rini Damayanti; Meny Sriwati; Sudirman; Nur Khaerat Nur; Mardewi Jamal (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
This study investigates the correlation between construction management efficacy and hydraulic design compliance with cost overruns in Indonesian Public-Private Partnership (PPP) water supply projects. Employing a mixed-methods approach, the research integrates quantitative analysis of official project data (contract values, DEDs, QC reports) with qualitative stakeholder insights. Key findings demonstrate a significant negative correlation between effective managerial oversight and cost overruns (r = -0.632), and similarly, between strict hydraulic adherence and cost overruns (r=-0.527). Unforeseen site conditions and design modifications were confirmed as significant exacerbating factors. The results highlight the imperative for integrated risk management, combining rigorous managerial scrutiny and unwavering technical discipline to mitigate budgetary risk. Policy recommendations emphasize enhancing inter-stakeholder coordination, enforcing technical standards, and leveraging digital monitoring tools to improve PPP project efficiency and sustainability.